The immunological link between neonatal lung and eye disease. Issue 8 (25th August 2021) - Wickramasinghe, Lakshanie C; van Wijngaarden, Peter; Tsantikos, Evelyn; Hibbs, Margaret L
Abstract: Bronchopulmonary dysplasia (BPD) and retinopathy of prematurity (ROP) are two neonatal diseases of major clinical importance, arising in large part as a consequence of supplemental oxygen therapy used to promote the survival of preterm infants. The presence of coincident inflammation in the lungs and eyes of neonates receiving oxygen therapy indicates that a dysregulated immune response serves as a potential common pathogenic factor for both diseases. This review examines the current state of knowledge of immunological dysregulation in BPD and ROP, identifying similarities in the cellular subsets and inflammatory cytokines that are found in the alveoli and retina during the active phase of these diseases, indicating possible mechanistic overlap. In addition, we highlight gaps in the understanding of whether these responses emerge independently in the lung and retina as a consequence of oxygen exposure or arise because of inflammatory spill‐over from the lung. As BPD and ROP are anatomically distinct, they are often considered discreet disease entities and are therefore treated separately. We propose that an improved understanding of the relationship between BPD and ROP is key to the identification of novel therapeutic targets to treat or prevent both conditions simultaneously. Abstract : In this review, we have explored the immunological link between two neonatal conditions known as bronchopulmonary dysplasia and retinopathy of prematurity, highlighting shared disease pathways, which include oxidative stress, proinflammatory cytokine production and trafficking of innate immune cells to affected tissue. A clear link between these two diseases is evident, indicating that a unified strategy could be used to treat both simultaneously.